Bioimaging: Employing Tryptone as a General Phase Transfer Agent to Produce Renal Clearable Nanodots for Bioimaging (Small 30/2015). Issue 30 (August 2015) - Liu, Fuyao; He, Xiuxia; Zhang, Junping; Zhang, Huimao; Wang, Zhenxin
<x xml:space="preserve">Abstract</x> A simple, versatile, and inexpensive strategy is developed by H. Zhang, Z. Wang, and co‐workers for transferring small hydrophobic nanoparticles into an aqueous phase using raw tryptone as a phase‐transfer agent. On page 3676, using tryptone‐NaGdF4 nanodots as typical examples, the nanodots are found to have excellent colloidal stability, outstanding MRI‐enhancing performance, efficient renal clearance, are nontoxic, and have an EPR‐based tumor targeting ability. Furthermore, the as‐transferred hydrophilic nanodots can be readily adapted by additional functionalization for various bioapplications.